(3bhGYO GdCMcGe aj eYQaI GdMdGd hGdMQGes - (3GdMdj, CHh efUhQ, GHf GdeWgQ, LeGd GdOjf, GdMSf Hf jhSa Hf Ydj GHf GdeWgQ, J (B726(3g`s
(3ChdgG (B:s
(3GdMeO ddg (B... (3dNUJ ajg dH GdaJGhi NGUI hHjfJ ajg bhGYO CMcGe GdNGUI GLGHI dGdJeGS CMH GdfGS Edj hCYRge Ydj hgh GdhdO GdYRjR eMeO GdPj CQLhG ef Gddg Whd YeQg HYOj hCf jhSOfj aj dMOj hCf jJQMe Ydj HYO eeGJj (B...s
(3BNQgG (B:s
... (3GdPj jSJMb Hg GdTabI aMb GdTabI ddhGQK dG ddehUi dg GdJGSYI dh OaY Edjg eGdG hbGd GUQa HYVg Edi RjO hGdHGbj dc aeGJ bHd GdOaY GfYRd hdh bGd GOaY Edjg HYO ehJj de jfYRd (B. (3Je GdLRA GdChds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B2/ 227s
(3GdPQjYI (B17 ( 930)s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis